Persepsi Mahasiswa Terhadap Perencanaan Karir dalam Menghadapi Dunia Kerja - Nur Mida (Indo Publishing, 2026)
This study aims to examine the perceptions of final-year students in facing the world of work. The research uses a qualitative approach with in-depth interviews conducted with management students. The results show that students have a positive perception of the importance of career planning during college. However, some students feel not fully prepared due to a lack of work experience, technical skills, and self-confidence. Students also recognize the importance of developing soft skills such as communication, teamwork, and responsibility. In addition, universities are considered helpful in preparing students, although improvements are still needed in training and work experience programs.